Easy Protocol for Making at Home E-Sinapinic Acid Good Matrix for Neutral and Sulfated Carbohydrate MALDI-MS Analysis - Salum, Maria Laura (2015)
Since the introduction of 3,5-dimethoxy-4-hydroxycinnamic acid (SA) and α-cyano-4-hydroxycinnamic acid as matrices, the successful application of matrix assisted laser desorption/ionization mass spectrometry (MALDI-MS) started. Cinnamics can exist as two different geometric isomers, the E- and Z-forms. The commercially available cinnamics currently used as matrices are E-cinnamics; they do not perform well in general for carbohydrate analysis. Recently, Z-cinnamic acid properties for matrices were studied and compared with those of the corresponding E-isomer. For the analysis of neutral/sulfated carbohydrates the outstanding performance for Z-SA was demonstrated. As the synthesis of pure Z-cinnamic acids requires several steps and the manipulation of some not friendly chemicals (i.e., bad smelling organic amines, toxic compounds, organic solvents, etc.), here we describe a convenient new one-pot protocol to prepare in situ, in a methanolic solution of commercial E-acid (i.e., E-SA), a Z- + E- mixture by photoisomerization (UVB irradiation); then, the only step required is the addition of water to the irradiated solution to become ready as a matrix stock solution for MALDI experiments. This "photo-made at home" matrix performs carbohydrate analysis with similar results to the corresponding Z-acid. The results here show that this novel protocol is a tool of choice for the direct, rapid and sensitive detection of neutral and sulfated carbohydrates without any tedious Z-cinnamic acid preparation and isolation.